USES AND ADVANTAGES OF DISCOURSE MARKERS ON SPEAKING SKILL LEARNING AT PESANTREN-BASED ENGLISH COURSE - Athena, Tera (Universitas PGRI Adi Buana Surabaya, 2017)
Discourse markers often occur in the process of communicatingusing speaking skills. In this case, between the speaker and the listenerwill always give a sign as the indicators which show that they canunderstand each other. They can follow the conversation or the lecturingprocess. Both parties use discourse markers as an indicator of interest andunderstanding of what is being discussed. In this study, the researcherdescribes the variation of discourse markers in form of three language;English, Indonesia and Madura. The researcher has conducted three timesobservation and taken documentation on Pesantren-Based English course.The term pesantren is described as an Islamic boarding house wherestudents immerse themselves in a learning environment with Islamicvalues. English-based Pesantren has been chosen because all of thestudents and the teachers must speak English although they are doing dailyactivities. The observations were conducted at three teachers or familiarlycalled ustad in the morning hours at 06.00-07.30 and evening at 21.0022.30.The final result states that three teachers have used three kinds oflanguages namely DMs in English are; About, ok, Now, If, there, please,well, really, right, mhmmmm, so and right. While DMs in the form ofIndonesian is: bisa, coba, ya, apa, jadi, tapi. DMs is also used in form ofMadurese language, namely: mon, deddih and apahjiah. The result showsthat DMs have two functions namely textual function and interpersonalfunction.